Dreaming of animals: The animal in Freud's analysis of a phobia in a five-year boy and history of an infantile neurosis - De Chavez, Jeremy (Animo Repository, 2015)
This paper examines the relationship of Freudian Psychoanalytic Theory and animals by examining two of Sigmund Freud's Famous cases studies, Analysis of a Phobia in a Five-year Boy (Little Hans) and History of an Infantile Neurosis (Wolfman). Numerous critics have accused Freud of taming the possibly radical figure of the animal in dreams by containing them within the interpretive frame of the Oedipal complex. Conscripting the work of French psychoanalyst Jacques Lacan, this paper attempts to theorize a more enabling and productive way to think about the relation of Freudian theory with animals.